(untitled) (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Chronic diarrhea is insidious onset that persists for 14 days and more, usually of noninfectious origin. Chronic diarrhea in children is not an uncommon problem in our country. Objectives: Objective of this study was to evaluate children with chronic diarrhea by clinical-biochemical profile and outcome. Methods: It was a retrospective observational study done in the department of paediatric gastroenterology and nutrition, BSMMU. The study was done during January 2017 through December 2018. Forty-five patients diagnosed as chronic diarrhea between the ages of 6 months to 18 years were included in this study. We Clinical, laboratory data and outcome of patients were analyzed. Results: Mean age of children was 5.96±2.3 year, 60%(27) were male and 40% (18) were female. Among them under 5 years were 55%(25). All children presented with diarrhea (100%) along with fever (24%), FTT (22%), abdominal pain (20%) and weight loss (20%). About 58% of children had anemia and 14% had hepatomegaly and/or splenomegaly. Raised ESR (40%), leukocytosis (20%), thrombocytosis (16%), raised CRP (13%) and electrolyte imbalance (16%) were observed. Intestinal TB (18%) was the most common etiology of chronic diarrhea. Moreover, chronic constipation with fecal incontinence mimicking diarrhea (11%), IBD (9%), coeliac disease (8%), IBS (7%), HIV enteropathy (4%), primary immunodeficiency disorder (4%) were also found. Improvement of diarrhea was observed in 96% children, 4% patient died due to diarrhea-related complications. Conclusion: Chronic diarrhea in children is not uncommon in Bangladesh and diagnosis of etiologies are challenging. Intestinal tuberculosis found to be an important cause of chronic diarrhea in this study. Although in the majority of the cases, etiology could not be identified, some remote etiologies were found on this study, like chronic constipation with fecal incontinence mimicking diarrhea, IBD, HIV enteropathy, primary immunodeficiency. DS (Child) H J 2020; 36(1) : 46-51